2020
DOI: 10.1029/2019ja027551
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Imaging of Traveling Ionospheric Disturbances Using GNSS and Geostationary Satellite Observations

Abstract: Traveling ionospheric disturbances (TIDs) are the manifestations of atmospheric gravity waves in the ionosphere. These disturbances have practical importance because they affect satellite navigation technologies such as Global Navigational Satellite System (GNSS), causing degradation in precise positioning applications. They also have scientific significance as their generation mechanisms and propagation are not fully understood. While there are specific instruments that can measure TIDs in certain locations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The amplitudes of the large-scale TIDs are rather small compared to other storm perturbations (e.g., trough and BPD) and unlikely to be present in our tomography. Still, Bolmgren et al (2020) demonstrated that a 3D reconstruction of large-scale TID signatures is possible with tomography. A detailed discussion of all these large-scale storm effects is beyond the ambit of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitudes of the large-scale TIDs are rather small compared to other storm perturbations (e.g., trough and BPD) and unlikely to be present in our tomography. Still, Bolmgren et al (2020) demonstrated that a 3D reconstruction of large-scale TID signatures is possible with tomography. A detailed discussion of all these large-scale storm effects is beyond the ambit of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of TIDs can vary from 0-15% (Bolmgren et al, 2020). Over Northern Scandinavia, it is found that the TIDs occur predominantly during pre-midnight hours 18 -24 LT and their occurrence is scarce during post-midnight hours 0 -6 LT (Shiokawa et al, 2013).…”
Section: Ionospheric Effectsmentioning
confidence: 98%
“…These simple model calculations are representative of what can be expected. Furthermore, previous studies of ionospheric TIDs from Tromsø indicate that conducting the experiment during post-midnight hours in geomagnetically quiet periods is preferable in order to reduce the Doppler broadening effects caused by the ionosphere (Brekke, 2012). Moreover, EISCAT 3D can be used to accurately measure the ionospheric electron density during observations, which can then be used to correct for phase variations caused by the ionosphere.…”
Section: Ionospheric Effectsmentioning
confidence: 99%